Study of the Structural Properties of Recycling Polyethylene Terephthalate as a Matrix to Prepare Polymer Nano Composites with Nano Nickel Oxide Synthesized via Green Method - Abaas, Zeena Saad; Abbass, Nada Mutter (Iraqi Journal of Physics, 2025)
This work employs the green manufacturing of nickel oxide (NiO) nanoparticles using rosemary (Rosmarinus officinalis) extract as a bioreductant. The NiO nanoparticles were combined with recycled polyethylene terephthalate (rPET) to generate a composite material. Atomic Force Microscopy (AFM), scanning electron microscopy (SEM), Energy Dispersive X-ray (EDS), X-ray diffraction (XRD), Thermogravimetric analysis (TGA), and differential scanning calorimetry (DSC) were used to thoroughly examine the NiO/PET nanocomposite. AFM and SEM investigations confirmed NiO nanoparticles’ homogeneous distribution and surface shape inside the rPET matrix. EDX validated the elemental composition, whereas XRD revealed information about the crystalline structure of the produced nanoparticles and the nanocomposite. TGA and DSC were used to examine thermal stability and breakdown behavior, demonstrating the NiO/rPET composite’s improved thermal characteristics. The composite’s anti-corrosion ability was also investigated, and it showed a considerable increase in corrosive resistance when compared to pure rPET. This work emphasizes the feasibility of employing green synthesis methods to produce metal oxide nanoparticles and their application in improving the characteristics of polymer composites, notably their anti-corrosion capabilities.